Drug delivery by sonosensitive liposome and microbubble with acoustic-lens attached ultrasound: an in vivo feasibility study in a murine melanoma model - Jun Hong Park; Byung Chul Lee; Young Chan Seo; Jung Hoon Kim; Da Jung Kim; Hak Jong Lee; Hyungwon Moon; Seunghyun Lee (Scientific Reports, 2023)
Abstract Conventional chemotherapy methods have adverse off-target effects and low therapeutic efficiencies of drug release in target tumors. In this study, we proposed a combination therapy of doxorubicin (DOX)-loaded ultrasound (US)-sensitive liposomal nanocarriers (IMP301), microbubbles (MBs) under focused US exposure using convex acoustic lens-attached US (LENS) to tumor treatment. The therapeutic effects of each treatment in a murine melanoma model were evaluated using contrast-enhanced US (CEUS) and micro-computed tomography (micro-CT) imaging, bioluminescence and confocal microscopy imaging, and liquid chromatography–mass spectroscopy (LC/MS) analysis. Tumor-bearing mice were randomly assigned to one of the following groups: (1) G1: IMP301 only (n = 9); (2) G2: IMP301 + LENS (n = 9); (3) G3: IMP301 + MB + LENS (n = 9); (4) G4: DOXIL only (n = 9); and (5) G5: IMP301 without DOXIL group as a control group (n = 4). Ten days after tumor injection, tumor-bearing mice were treated according to each treatment strategy on 10th, 12th, and 14th days from the day of tumor injection. The CEUS images of the tumors in the murine melanoma model clearly showed increased echo signal intensity from MBs as resonant US scattering. The relative tumor volume of the G2 and G3 groups on the micro-CT imaging showed inhibited tumor growth than the reference baseline of the G5 group. DOX signals on bioluminescence and confocal microscopy imaging were mainly located at the tumor sites. LC/MS showed prominently higher intratumoral DOX concentration in the G3 group than in other treated groups. Therefore, this study effectively demonstrates the feasibility of the synergistic combination of IMP301, MBs, and LENS-application for tumor-targeted treatment. Thus, this study can enable efficient tumor-targeted treatment by combining therapy such as IMP301 + MBs + LENS-application.